Psychological crisis interventions with victims of the coronavirus pandemic - Petrović Nikola M. (Temida, 2020)
This paper deals with psychological crisis interventions in working with victims of coronavirus, i.e. all those who got sick, but also the entire population which is exposed to the potential danger of infection. It first analyzes the psychological consequences of the pandemic on people, and then the specifics of crisis interventions during the pandemic. The main subject of this paper is the analysis of the adequacy of the most often recommended psychological crisis intervention called psychological first aid for this global crisis. Authors suggest certain modifications of this intervention that could prove important in the coming period, since the end of the pandemic is not yet in sight.